The space-time dimension in the study of heritage categories - Cantar, Nahir Meline (2019)
Over time, the concept of cultural heritage has been broadened as new elements and diversity of contexts were incorporated into the discussion. In order to study the evolution of this concept, in this paper we analyze the charters, recommendations and doctrinal principles adopted by the International Council of Monuments and Sites (known as ICOMOS), focusing on their spatial conceptions and contrasting them with definitions of geographical space. From this analysis, three characteristic stages concerning the definitions of heritage in relation to its spatial dimension are detected. As a result of this analysis, it has been possible to generate a dialogue between both types of categories and contribute to their broader understanding, which can be useful not only as an analytical tool but also as a contribution to asset management. Finally, the expansion of the heritage concept is discussed in the framework of the criticisms that are made from different approaches to heritage activation processes at a global scale.